Proteomic Changes in Antioxidant System in Strawberry During Ripening - Song, Jun; CampbellPalmer, Leslie; Vinqvist-Tymchuk, Mindy; Fillmore, Sherry; Forney, Charles; Luo, Honghui; Zhang, Zhaoqi (Frontiers in Plant Science, 2020)
Quantitative proteomics has become a powerful post genomic tool to study biological samples. To investigate the strawberry antioxidant defense system during fruit ripening, a targeted quantitative proteomic approach using multi reaction monitoring (MRM) was developed to investigate targeted proteins in the antioxidant enzyme system in strawberry fruit. We investigated 46 proteins and isoforms with 73 identified peptides which may be involved in this antioxidant enzyme system. Among the proteins that changed during ripening, aldo/keto reductase (AKR), superoxide dismutase (SOD) and glutathione transferase (GT) increased significantly, while dehydro-ascorbate reductase, 2-Cys peroxiredoxin, catalase (CAT), 1-Cys peroxiredoxin and L-ascorbate peroxidase (APX) decreased significantly. These results suggest that fruit ripening of strawberry activates the enzymes of an SOD/glutathione metabolism system. The methodologies used in this study will be useful for systematically characterizing the role of antioxidant enzymes in fruit ripening of other plants.